Leerstof onder andere voor[br][math]\oplus[/math] ingangsexamen geneeskunde
[math]\begin{tabular}{l}[br]1.\;e^m\cdot e^n=e^{m+n}\\[br]2.\; \left(e^m\right)^n=e^{mn}\\[br]3.\; \frac{e^m}{e^n}=e^{m-n}\\[br]4.\;e^{-m}=\frac{1}{e^m}\\[br]5.\;e^{\frac{1}{n}}=\sqrt[n]{e}\\[br]6.\; e^0=1\\[br]7.\;e^{\frac{m}{n}}=\sqrt[n]{e^m}=\left(\sqrt[n]{e}\right)^m[br]\end{tabular}[/math]
[math]\begin{tabular}{l}[br]1.\; \ln(xy)=\ln(x)+\ln(y)\\[br]2.\; \ln\left(\frac{x}{y}\right)=\ln(x)-\ln(y)\\[br]3.\; \ln\left(x^r\right)=r\cdot\ln(x)\\[br]4.\;\ln\left(e^x\right)=x\\[br]5.\; e^{\ln(x)}=x\\[br]6. \;\ln(e)=1\\[br]7.\;\ln(1)=0[br]\end{tabular}[/math]
Als [math]e^{\lambda}=4[/math], dan is [math]e^{\frac{3}{2}\lambda}[/math] gelijk aan
[math]e^{\frac{3}{2}\lambda}=\left(e^{\lambda}\right)^{\frac{3}{2}}=(4)^{\frac{3}{2}}=\sqrt{4^3}=8[/math]
Als [math]f(x)=e^{4x-3}[/math], dan is [math]f(1-\ln\left(\frac{1}{x}\right))[/math] gelijk aan
[math]f(1-\ln\left(\frac{1}{x}\right))=f(1-(\ln(1)-\ln(x)))=f(1+ln(x))=e^{4(1+ln(x))-3}=e^{1+4\ln(x)}=e\cdot\left(e^{\ln(x)}\right)^4=e\cdot x^4[/math]
Vereenvoudig [math]e^{2\ln(3)+1}[/math]
Welke waarde neemt de uitdrukking [math]\frac{e^{3x}-e^{-3x}}{e^{3x}+e^{-3x}}[/math] aan als [math]x=\ln(\sqrt{3})[/math]?
[math]\frac{e^{3x}-e^{-3x}}{e^{3x}+e^{-3x}}=\frac{e^{-3x}(e^{6x}-1)}{e^{-3x}(e^{6x}-1)}\Rightarrow \frac{e^{6\ln(\sqrt{3})}-1}{e^{6\ln(\sqrt{3})}+1}=\frac{e^{\ln\left(3^{\frac{1}{2}}\right)^6}-1}{e^{\ln\left(3^{\frac{1}{2}}\right)^6}+1}=\frac{27-1}{27+1}=\frac{13}{14}[/math]